Hydrophysical, chemical and microbial properties of imported green waste composts - SAIFELDIN A.F. EL-NAGAREABI; ABDULKADIRI E. ELSHAFIE; HUDA ALBURASHDI (Nusantara Bioscience, 2014)
Abstract. El-Nagerabi SAF, Elshafie AE, Alburashdi H. 2014. Hydrophysical, chemical and microbial properties of imported green waste composts. Nusantara Bioscience 6: 13-18. To study the hydrophysical, chemical and microbial properties of the imported green waste composts (GWCs) and their suitability as an alternative to agrochemicals, four types of GWCs (Florabella, Mikskaar, Potgrond, and Shamrock) were selected. All composts showed normal physical properties, except weed seeds in Shamrock. The germination indexes comparable to the standard (90%) were 100% for Mikskaar followed by Florabella (97%), Potgrond (95%), and Shamrock (92%). Variations in physicochemical properties were shown as acidic pH 5.1-6.5 (standard 5-8), electrical conductivity (EC) 0.8-1.8 mScm-1 (standard 0.0-4.0 mScm-1), moisture content (MC) 54-70.5% (standard 35-60%) and water holding capacity (WHC%) 400-800%. The chemical properties were expressed as ammonia concentrations 2871-6565 mg kg-1 (standard <500 mg kg-1), organic matter 53.3-66.2% (standard 35%). The concentrations of heavy metals (Zn, Ni, Pb, Hg, As, Cd, and Cr) were lower than the recommended levels. The bacterial colony forming unit per gram compost ranged between 330-2870 cfu/g, the most probable number (MPN) for coliform bacteria was 23-460 cfu/g, whereas the fungal cfu were 30-1800 cfu/g. Aspergillus niger was the predominant fungus recovered from all compost samples (100%), followed by A. fumigatus (75%), whereas A. sparsus, A. versicolor and yeasts (50%), and the remaining species of the genus Acremonium sp., Aspergillus flavus, A. restrictus, Cladosporium spp., and Penicillium spp. recovered from 25% of the samples. Generally, these composts revealed normal hydrophysical properties with obvious variation in moisture contents and elevated chemicals and microbial contamination. Therefore, there is an urgent need for quality control measurements and restrict abide to legislations and quarantine regulations.